The response of the lactate minimum test to a 12-week swimming training - Campos, Eduardo Zapaterra [UNESP] (2014)
Despite the utilization of lactate minimum test (LMT) in training, its intensity response to training remains controversial. The aim of the present study was to verify alterations of LMT intensity in swimmers during a 12-week training protocol. Eight swimmers were submitted to three LMT assessments: beginning of the season, T0; after four, T4; and twelve weeks, T12. The LMT consisted of a 200m maximal effort and, after eight minutes of passive rest, five incremental stages of 200m swimming. The intensities of the incremental stages were defined subjectively (“very light,” “light,” “moderate,” “hard,” and “all-out”). The training was divided in two blocks of periodization: endurance training period (ETP, T0 – T4), and quality plus taper period (QTP, T4 – T12). The LMT intensity of T4 and T12 were significantly higher than T0. We conclude that LMT is modified due to swimming training and can be used for training prescription and detection of aerobic capacity alterations during a season.